Automated Training of Deep Convolutional Neural Networks for Cell Segmentation - Sajith Kecheril Sadanandan (Nature Portfolio, 2017)
Abstract Deep Convolutional Neural Networks (DCNN) have recently emerged as superior for many image segmentation tasks. The DCNN performance is however heavily dependent on the availability of large amounts of problem-specific training samples. Here we show that DCNNs trained on ground truth created automatically using fluorescently labeled cells, perform similar to manual annotations.